Eksplorasi Pengalaman Crossdressing di Komunitas Cosplayer Jakarta - Anastasya Putri; Nursanti, Siti; Flori Mardiani Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Crossdresser, or known as cross-dresser, is an act where someone wears clothing, adopts appearances, and exhibits behavior aligned with a gender different from their own biological sex, usually influenced by specific cultural norms. This research aims to delve into and uncover the experiences of individuals involved in crossdressing practices within the cosplay community in Jakarta. Through a phenomenological approach, this study explores the motives, pleasurable experiences, and challenges in the lives of crossdressers within the cosplay group in Jakarta. In this research, the researcher employs a qualitative approach. The theories used in this study are phenomenology and social identity theory. The research findings indicate that crossdressers face quite complex dynamics in their journeys. Each crossdresser has different experiences. Comfort, entertainment, and a means of self-expression are the primary motives expressed by crossdressers. The cosplay group also plays a role in the development of the social identity of crossdressers, helping them better understand themselves and others.